Water Quality Status and Pollution Prevention Measures of Rivers Flowing into the Sea via the Pearl River Estuary - WANG Shenfang; MA Haitao; SHAO Wei (Renmin Zhujiang, 2025)
The water quality of rivers discharging into the sea is a critical factor influencing the estuarine water environment, directly impacting regional water security. This study assessed the monthly water quality status of major rivers flowing into the sea via the Pearl River Estuary using the single-factor index method. Targeted improvement measures were proposed based on identified exceedance factors and their causes. Results indicate that the current water quality of the 11 major rivers flowing into the sea via the Pearl River Estuary in 2024 is not optimistic. The main exceedance factors are total nitrogen, dissolved oxygen, and total phosphorus. The main sources of pollution are urban sewage treatment plants, integrated sewage treatment facilities, centralized treatment plants of industrial wastewater, scattered domestic sewage, and aquaculture wastewater. To further enhance the water security in the Pearl River Estuary area, it is necessary to significantly increase the collection and treatment rate of regional sewage and wastewater, further strictly control the wastewater discharge from highly polluting enterprises, and vigorously promote healthy and ecological farming models. The research results can provide decision-making references for the water environmental protection and management of the Pearl River Estuary.